ANALISIS BONUS DEMOGRAFI SEBAGAI KESEMPATAN DALAM MENGOPTIMALKAN PEMBANGUNAN PERTANIAN DI SUMATERA BARAT - Yusmarni, Yusmarni (Jurnal AGRISEP, 2016)
Demographic dividend is a dynamica in demographic that accurs due to the change of demographic structure based on age, where the number of productive population is higher than un-productive populatian. Indonesia has experiancing this conditian since 2015 untill 2035. Although west Sumatera is not fully experiancing demographic dividend, this conditions still offers an opportunity to improve welfare and promote a better economic development by improving and optimalizing the development of economic sector. Since agricultural sector is the biggest sector contributing to GDP and absorb labour in West Sumatera, the goverment should optimalize the develpment of this sector. Beside that, West Sumatera is a hinterland area (LQ=1,750) that can provide agricultural commodity for other provinces. Assumingly that the requarement of a good quality of human resource is fulfilled, the ability to purchase of  the productive population in Indonesia will increase and create more demand for good quality of agricultural commodities. Additionally, this condition is an opportunity of West Sumatera to develop sub-sector of agroindutry in order to create value added of agricultural commodity. The development of agroindustry not only will increase farmers income in rural area but also will reduce un-employment in West Sumatera.